Paratesticular Inflammatory Myofibroblastic Tumor in a Pediatric Patient - Miriam Harel; John H. Makari (Case Reports in Urology)
Although rare, paratesticular inflammatory myofibroblastic tumor (IMT) represents the second most common paratesticular mass after adenomatoid tumor and comprises roughly 6% of such lesions. Only approximately four cases have been reported in patients younger than 18 years of age. We report an incidentally discovered paratesticular IMT in a 17-year-old male successfully treated with wide excision and testis sparing. To our knowledge, no recurrence has been reported after complete excision of paratesticular IMT; however, continued follow-up is recommended.